A variação da lateral palatal na Cidade de Goiás - Lima, Joeline de Barros (2024)
The aim of this study is to investigate the variable realization of the segment /ʎ/ in Cidade de Goiás, a city located in Goiás state (Brazil), from the data collected by the Functionalist Group (Grupo Funcionalista) of Federal University of Goiás. We consider, to this investigation, some linguistic aspects as antecedent and following phonological contexts, the stress and syllable tonicity, in adittion to three social factors as the interviwee's gender, age and level of education. For the variable analises of the palatal lateral /ʎ/, we chose the consonant /ʎ/ full realization, the vocalization in [j] and erasure (Ø). In order to describe and analyse this phonological phenomenon, as well as to identify internal and external motivations to the system, we use as guide Labov's variation and change theories (Labov, 2008). The rules of categorical nature will be presented according to the phonological theory of Feature Geometry (Clements; Hume, 1995) and the data will be statistically treated through the software RStudio. The results found allow us to associate, as proposed by Soares (2008), both linguistic and extralinguistic aspects, from the loss of phonetic features to issues related to social factors such as age and sex, in this study.